Upaya Meningkatkan Kemampuan Membaca melalui Media Permainan Kartu Bergambar - Poniman Poniman (Jurnal KIBASP (Kajian Bahasa, Sastra dan Pengajaran), 2018)
This study aimed to describe how was the used of flash card for the first graders of SDN 133 Seluma and to improve early reading ability in Bahasa Indonesia. This is action research study with 2 cycles which has three meetings in each cycle and there were ten students as participants. Before treatment, the percentage of learning mastery was 50%. The learning mastery improved 70% in cycle I after giving treatment then it also improved 80% in cycle II, therefore the researcher decided not to continue to cycle III. In conclusion, using flash card in learning process could solve students' difficulties in early reading stage of first graders of SDN 133 Seluma. Keywords: Flash card, reading